SUPERVISI AKADEMIK KEPALA SDN 01 BUJUK AGUNG KECAMATAN BANJAR MARGO KABUPATEN TULANG BAWANG - Yuri Anton (UNISAN JURNAL, 2024)
This research aims to investigate the implementation of academic supervision by the school principal in improving the quality of learning at SDN 01 Bujuk Agung Tulang Bawang. The research method used is a case study with a qualitative approach. Data was collected through observation, interviews and analysis of related documents. The research results show that the implementation of academic supervision by the principal at SDN 01 Bujuk Agung Tulang Bawang can be characterized as structured and sustainable. The program includes supervision program development, teacher involvement, implementation of feedback, and use of relevant data and evidence. Effective communication between school principals and teachers, leadership skills, commitment and support, availability of resources, and understanding of supervision are factors that influence the effectiveness of academic supervision. The impact of academic supervision can be seen in improving teaching skills, motivation and the quality of teacher learning. Apart from that, positive impacts can also be seen on student learning achievement, including increased test scores, understanding of concepts, and interest in learning.